Formal Development of System of Systems. (27th August 2013) - Kamali, Maryam; Neovius, Mats; Petre, Luigia; Sandvik, Petter
Abstract : Characterising for contemporary systems is their dependence on constituent systems to provide information, functionality, and scalability. Moreover, as the tasks that systems perform are ever more intimate and critical in their nature, reliability and correctness are great concerns. On these matters, we outline a methodology for formal integration of systems. We claim this formal approach to assist in managing the complexity and correctness, in preserving reliability and in respecting the independence of the constituent systems. As a proof of concept, we integrate two in-house control systems specified independently in the Event-B language with the Rodin Platform tool. Moreover, we show how to introduce a new functionality that is only possible due to the integration. Hence, we formally construct a system of systems and provide the methods for hierarchical integration of those.